Analisis Sentimen Ulasan User Terhadap Aplikasi Tix-Id Menggunakan Metode Naïve Bayes Pada Google Play Store - Java Khitamasari; Isa Faqihuddin Hanif (Jurnal ICT: Information Communication & Technology, 2023)
The TIX-ID application is an application-based online cinema ticket booking application. The TIX-ID application can be downloaded and accessed anywhere and anytime. The TIX-ID application is also available on the Google Play Store and Appstore. The development of online cinema ticket purchasing applications in Indonesia is growing rapidly, customers buying cinema tickets online continue to increase and feel satisfied every month. In choosing an application that makes it easy to buy cinema tickets online, users usually consider the ease of using the application, security, and available promotions. But there are still some users who are not satisfied with the services and features available in the TIX-ID application. So from these problems, sentiment analysis research was carried out to produce a classification on user satisfaction with the TIX-ID application using the Naïve Bayes method which has high accuracy with a simple and fast process. This research stage consisted of collecting data using Web Scraping, carrying out the Dataset Preprocessing stage, carrying out the TF-IDF word weighting stage and the last stage was implementing the algorithm. The data obtained from the web scraping stage is as much as 1,600 user commentary data with a total of 1,259 positive sentiment data and a total of 334 negative sentiment data. The accuracy value obtained after implementing the Naïve Bayes algorithm obtained a percentage of 71.77% and it can be seen that this data can be used as a reference for TIX-ID application developers to make considerations to provide even better service.